CHALLENGES OF INITIATING GROWTH HORMONE THERAPY IN TURNER SYNDROME WITH CHIARI MALFORMATION: A FOLLOW UP REPORT - AS, Amir Hamzah Maju; MI, Muntari; M, Noordin; NS, Mohd Nor (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Turner syndrome (TS) associated with congenital central nervous system abnormalities are uncommon. Study on outcome of growth hormone therapy in this group are limited. We present a follow up report on challenges of growth hormone (GH) therapy in our patient with Turner Syndrome (45, XO) and Type I Arnold Chiari Malformation. CASE NB is a 17-year-old female who was first referred to us for short stature and dysmorphism. Karyotype confirmed 45, XO, hence, TS diagnosis was made. She was pre-pubertal at presentation, with height of 132 cm (-4.98 SDS), and mean parental height of 153 cm. Her bone age was delayed at 12.5 years. She was planned for GH therapy. Polysomnography (PSG) revealed an incidental finding of central apnoea with Apnoea-Hypopnea Index (AHI) of 22.5/H. This led to a brain MRI which revealed cerebellar tonsils descended 7 mm below the foramen magnum, consistent with Type I Arnold Chiari malformation. A repeat PSG showed significant improvement of her AHI index. Following multidisciplinary discussion, a decision was made for GH therapy. She was started on GH therapy and the dosage was gradually titrated. After 3 months of GH therapy, her height velocity improved from 2.7 cm/year to 5.2 cm/year. She remained well, however a PSG post-GH therapy revealed worsening apnoea. Family counselling was done, and her parents were not keen to continue with GH therapy. CONCLUSION TS with Chiari malformation is uncommon. Commencement of GH therapy in this group requires multidisciplinary management. Close surveillance of potential side effects is crucial to avoid potential adverse events.